The educational institution and the school community: literature review (Research, Society and Development, 2020)
Changes in thought paradigms have always boosted transformations in the scientific-technological sphere and reached the economic, social and educational sectors. Thus, these changes stimulate new forms of relationship between knowledge, know-how and technique, in the complex dynamics of producing knowledges, in the contemporary world. These new forms of (re) construction of information, knowledge and knowledge permeate the re (elaboration) of a pedagogical/educational project that articulates education for citizenship, for intellectuality and also for work. Thus, the discussions about the public policies of education are originated, in the face of universalization, democratization and permanence of the student in the school environment. Therefore, the objective of the article, which is presented, investigates the social attributions of school education institutions. For this purpose, we used the bibliographic and exploratory research to perform the literature review. The article addressed as a result high school and school curriculum, highlighting that the school is not just about students and teachers. The schools have an amalgam that makes up their community: students, managers and teachers, besides the family. Finally, the school community must provide training for the labour market, a training that integrates the student body in social, political and democratic participation.